Pipelines for water conveyance and drainage - Beieler, Roger W., editor; Environmental and Water Resources Institute (U.S.). Task Committee on Pipelines for Water Conveyance and Drainage (Reston, Virginia : American Society of Civil Engineers, 2013)
Includes bibliographical references and index